An Update on Secondary Bacterial and Fungal Infections and Their Antimicrobial Resistance Pattern (AMR) in COVID-19 Confirmed Patients - Boorgula, Sushma Yadav; Yelamanchili, Sadhana; Kottapalli, Pragathi; Naga, Mohini D. (Journal of Laboratory Physicians, 2022)
Introduction Since coronavirus disease 2019 (COVID-19) has limited treatment options, concern has been raised over secondary infections and antimicrobial resistance (AMR) patterns. It has been observed that patients who were infected with COVID-19 were predisposed to develop secondary infections. The purpose of the study is to ascertain the prevalence of the bacterial and fungal coinfections in COVID-19 patients, and also to assess the AMR patterns in the obtained isolates.Methods We have studied 200 clinical samples obtained from 122 COVID-19 positive patients. Pathogens were identified using Vitek 2 system. The demographic and clinical patterns were also observed.Results A total of 122 patients developed secondary infections. Patients aged more than 40 years were majorly affected (p-value < 0.0001). Respiratory samples (n = 96) were predominant. Klebsiella pneumoniae (n = 68) was the most common pathogen isolated followed by Acinetobacter baumannii (n = 54) and an overall 6% rise in the Carbapenem resistance was observed in the isolates.Conclusion To contain the secondary infections in COVID-19 patients, it is imperative to adhere to antimicrobial stewardship program and timely revise the empirical antibiotic policy.
Keywords: antimicrobial resistance; coagulase-negative staphylococcus; central line associated bloodstream infections